The Social Science of Institutional Transformation: Intersectional Change in the Academy - Morimoto, Shauna A. (Frontiers in Sociology, 2022)
This article examines intersectional praxis as an approach to institutional transformation, arguing that intersectionality is both a catalyst for and outcome of gender equity efforts in academic STEM fields. As such, approaching gender equity intersectionally can be understood as a way that theory and practice are co-constitutive of scientific academic fields and hence an important aspect of transforming academic institutions. By adopting intersectionality in programs for equity to address foundational aspects of knowledge, I argue that social sciences have paved the path for institutional change. Grounding my discussion in a case study of the NSF ADVANCE institutional transformation program, I begin with an overview of ADVANCE goals for gender equity through systemic change in academic STEM fields. I consider how social science informed the project of institutional transformation, paying particular attention to the second phase of ADVANCE, wherein intersectionality became a cornerstone of the equity program. By analyzing ADVANCE programs intersectionally, I attend to the processes of struggle over power and oppression, arguing that transformation occurs through the intersectional production of knowledge. Exploring these connections shows how social science is inherent in intersectional equity in STEM fields and transforming academic institutions.